Determination of inorganic arsenic [As(III) & As(V)] by square wave cathodic stripping voltammetry - Lim, Poh Moy (Universiti Malaysia Sarawak, (UNIMAS), 2004)
Arsenic contamination has become a worldwide problem. Many of the arsenic poisoning from natural arsenic in the drinking water occur in poor countries without the necessary infrastructure to be able to respond rapidly. Accurate, reliable, sensitive, convenient analytical procedures with low economic outlay in capital cost are, therefore of crucial significance for monitoring tasks in environmental protection of natural waters as well as in identifying any contaminated waters rapidly. In this study, a simple, fast and sensitive method using square wave cathodic voltammetry at a hanging mercury drop electrode was modified and optimized for the determination of As(III) and total inorganic arsenic in environmental samples. For As(III) determination, a newly optimized condition was achieved using simplex optimization method, aided by the Multisimplex 2.1 software programme. Five factors contributed to the performance of the method were optimized. They were Cu(II) concentration, deposition potential, deposition time, pulse amplitude, and frequency. It was found that 20 ppm of Cu(II) and 60 s of deposition time gave the highest peak currents. Preconcentration was carried out in 1M HCl and 20 ppm Cu(II). The optimized instrumental parameters were set at the deposition potential of -0.35 V versus Ag/AgCl (3 M KCD, pulse amplitude of 0.06 V, frequency of 149 Hz, and 55 s of accumulation time. The deposited intermetallic compound was reduced at a potential of about -0.80 V versus Ag/AgCl (3 M KCL). The detection limit was 0.05 μg/L for 5 μg/L of As(III) at 55 s deposition time. The low detection limit at less than 1 minute of deposition time had surpassed many other similar methods. The linearity range up to 700 μg/L was a great advantage to quantifying the wider concentration range of the environmental samples without the need of dilution. Though deoxygenation was not necessary, it was found to increase the sensitivity by lowering the baselines of the background currents. Therefore, depending on the concentration, analysis time may be saved on the omission of the deoxygenation step. In the determination of total inorganic arsenic, the reducing effects of thiocyanate and thiosulfate ions were investigated. Thiocyanate needed a long time to reduce As(V) to As(III) while thiosulfate was found to be a faster and more effective reducing agent. Only 2 mM of thiosulfate was needed to reduce As(V) to As(III) effectively. The presence of 0.1 to 0.5 mM of thiocyanate was found to improve the peak width as well as the sensitivity. At higher thiocyanate concentrations, the baselines became higher on the right side of the peaks. This was attributed to the complexes formed between Cu(II) and thiocyanate ions. In the presence of thiosulfate and thiocyanate ions, the deposition potential at -0.5 V produced the highest peak current and the best-defined peak shape. The Cu(II) concentration at 40 ppm was found to give the best and well-resolved peaks. Therefore, for total inorganic arsenic determination, preconcentration was carried out in 1M HCI, 40 ppm Cu(II), 2 mM thiosulfate, 0.1 - 0.5 mM thiocyanate, and at a potential of -0.5 V versus Ag/AgC1 (3M KC1). Deoxygenation was not needed as it did not increase the sensitivity of the peak currents. The detection limit was 0.2 gg/L and the relative standard deviation was calculated at 4.3 % (n=10) for 2 μg/L of As(V) and at 55 s deposition time. The interference studies were done on a few ions commonly found in natural waters. No significant interference was observed for ions Hg2+, Zn2+, Mn2+ and EDTA present at 1 ppm concentration level except Fes* that caused more than 30 % suppression on the peak height. The method was applied in the analysis of environmental samples from Sungai Juhara and Tasik Biru, Bau, Sarawak. Statistic analysis suggested that the SWCSV method under study was comparable to the established GFAAS method. The results showed that all of the samples contained total inorganic arsenic about 3- 30 times higher than the maximum of 10 ppb As in the drinking water, the recommended value by WHO. All the samples had 1- 26 % of the total inorganic arsenic existed in very toxic As(III) species. Analysis on the digested samples found the presence of organoarsenic compounds. It can be concluded that the newly optimized method consists of the criteria for a good analytical technique and can be adapted for routine analysis.